Quantification of lignans in 30 ground coffee samples and evaluation of theirs extraction yield in espresso coffee by HPLC-MS/MS triple quadrupole. (17th February 2020) - Angeloni, Simone; Navarini, Luciano; Khamitova, Gulzhan; Sagratini, Gianni; Vittori, Sauro; Caprioli, Giovanni
Abstract: Lignans are a class of polyphenols considered to be phytoestrogens because of their oestrogenic/antiestrogenic activities and their plant origin. Few works have reported on the content of lignans in ground coffee, and most of them analysed a small number of samples. Hence, our aim was to quantify the content of three lignans, secoisolariciresinol, lariciresinol and matairesinol, in ground coffee by using high-performance liquid chromatography tandem mass spectrometry. Evaluation of acidic hydrolysis, methanolic extractions, and enzymatic digestions as extraction methods indicated that enzymatic digestion with Taka-diastase 2% was the best. When this method was applied to 30 different ground coffees, we found that SECO was the highest concentration lignan (84.4–257.8 μg kg −1 ), followed by LARI (26.1–91.5 μg kg −1 ). Moreover, comparison of lignan extraction yield in espresso coffee and ground coffee showed that these molecules seem to be completely extracted during espresso coffee percolation, since the extraction yield average was 95.2%.